2020
DOI: 10.1111/acer.14332
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Perinatal Alcohol Exposure and Perinatal Marijuana Exposure on Adult Neurogenesis in the Dentate Gyrus

Abstract: Background: Marijuana and alcohol are both substances that, when used during pregnancy, may have profound effects on the developing fetus. There is evidence to suggest that both drugs have the capacity to affect working memory, one function of the hippocampal formation; however, there is a paucity of data on how perinatal exposure to alcohol or cannabis impacts the process of adult neurogenesis.Methods: This systematic review examines immunohistochemical data from adult rat and mouse models that assess perinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“… 73 This might be because maternal prenatal cannabis use adversely affects growth of fetal and adolescent brains, 29 , 55 as demonstrated in the reduction of inhibitory interneurons in the hippocampal formation of adult rats. 74 In more serious cases, children raised in families where there is substance misuse can suffer negative effects on long-term health and well-being. 75 Parents may be unable to supervise their children and meet their needs appropriately, which could lead to emotional abuse and neglect.…”
Section: Methods and Findingsmentioning
confidence: 99%
“… 73 This might be because maternal prenatal cannabis use adversely affects growth of fetal and adolescent brains, 29 , 55 as demonstrated in the reduction of inhibitory interneurons in the hippocampal formation of adult rats. 74 In more serious cases, children raised in families where there is substance misuse can suffer negative effects on long-term health and well-being. 75 Parents may be unable to supervise their children and meet their needs appropriately, which could lead to emotional abuse and neglect.…”
Section: Methods and Findingsmentioning
confidence: 99%
“…Evidence in several rodent models has shown that EtOH produces cognitive impairment in hippocampal‐dependent tasks and that the damage varies according to the stage of development at which the rodent was exposed to EtOH and the dose (Table 3) (Mira et al, 2020; Reid et al, 2020; White et al, 2000). As brain development persists during childhood and adolescence in mammals, alcohol consumption is not only risky during the prenatal stages but adolescence as well (Table 3).…”
Section: Relationship Between Alcohol Memory Consolidation and Hippoc...mentioning
confidence: 99%
“…We have recently published a systematic review (126) that suggested that hippocampal interneurons may be a focal point for the actions of both THC and ethanol in the developing brain. In part, this is because THC activates CB1 receptors, which can change GABA release, and further.…”
Section: Introductionmentioning
confidence: 99%